SIKAP POLITIK ELIT NU PASCA KEMBALI KE KHITTAH DI KABUPATEN WONOSOBO TAHUN 1984-1998 - Imam, Faizal (Journal of Indonesian History, 2014)
NU in Wonosobo was established in 1933. NU Wonosobo branch was established to spread Islam in accordance with the understanding of ahlussunnah wal Jama'ah. That role is run by clerics who are in NU. Kyai in NU itself has a very important role, because it acts as elite clerics in the NU but also as a leader in the community. Every decision or position that is taken by the clerics will influence the students and also for local people, including attitude in politics. Figures who contributed to the establishment of a branch NU Wonosobo include Sayyid Ibrahim, KH Kyai Abu Jamroh and Kyai Hasbillah Bumen. Wonosobo NU itself visible role when joining the Hezbollah and Sabilillah in maintaining the independence of Indonesia. Before Khittah figures NU elite joined the PPP as a manifestation of their support for the PPP as a party fusion. Basically the political elite, NU Wonosobo, reflecting the dynamics of politics in Wonosobo regency itself. Stance taken NU elite who joined Golkar (KH Muntaha and KH Habib Idris) is a political strategy, where the entrance to the government system, the ideas can be heard while the citizens Nadliyin elite survive in PPP (KH Zainuddin and KH Ibrahim) after Khittah based because PPP remains the Islamic party that must be fought. The impact of each of the political attitudes of NU elite in Wonosobo, making some aspects of change, such as the impact of the government, NU organizations, political parties, and political choices Nahdliyin Â